2022
DOI: 10.1155/2022/4461165
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Attraction Recommendation Method Based on Megadata and Artificial Intelligence Algorithm

Abstract: As China’s economy continues to grow of informational technology and mobile Internet industry, the online tourism industry has received more and more extensive attention and use. However, as an emerging industry, users often need to spend a lot of time to choose travel services that match their needs because of the complex amount of relevant information. Under such circumstances, this paper studied the recommendation method in travel platform. First, the big data is used to extract user data. Secondly, the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…4.6.6. Superiority of the Proposed Algorithm Through analysis, it can be concluded that the proposed algorithm has significant advantages over the methods used in the literature [5][6][7][8][9][10][11][12] and the commonly used electronic map methods used in tour route planning, as follows:…”
Section: Analysis Of the Comparison Of Three Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…4.6.6. Superiority of the Proposed Algorithm Through analysis, it can be concluded that the proposed algorithm has significant advantages over the methods used in the literature [5][6][7][8][9][10][11][12] and the commonly used electronic map methods used in tour route planning, as follows:…”
Section: Analysis Of the Comparison Of Three Methodsmentioning
confidence: 99%
“…Yun et al [5] used the Naive Bayes model to evaluate users' interests. This method finally improved the collaborative filtering algorithm's performance and increased the recommendation accuracy.…”
Section: Analysis Of Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, social media platforms further promote efficiency and matching, 10 thereby increasing user visits and retention rates on these platforms. 11 …”
Section: Introductionmentioning
confidence: 99%